Biologic drug survival rates in the era of anti‐interleukin‐17 antibodies: a time‐period‐adjusted registry analysis. (22nd February 2021) - Graier, T.; Salmhofer, W.; Jonak, C.; Weger, W.; Kölli, C.; Gruber, B.; Sator, P.G.; Prillinger, K.; Mlynek, A.; Schütz‐Bergmayr, M.; Richter, L.; Ratzinger, G.; et al.
Summary: Background: Drug survival rates reflect efficacy and safety and may be influenced by the availability of alternative treatment options. Little is known about time‐dependent drug survival in psoriasis and the effect of increasing numbers of biologic treatment options. Objectives: To determine whether drug survival is influenced by the availability of treatment options and by factors such as gender, psoriatic arthritis or previous biologic treatment. Methods: This observational, retrospective, multicentre cohort study analysed data from patients registered in the Austrian Psoriasis Registry (PsoRA) who were treated with biologics between 1 January 2015 and 30 November 2019. Results: A total of 1572 patients who received 1848 treatment cycles were included in this analysis. The highest long‐term Psoriasis Area and Severity Index improvement was observed after treatment with ixekizumab, followed by ustekinumab and secukinumab, adalimumab and etanercept. Overall, ustekinumab surpassed all other biologics in drug survival up to 48 months. However, when adjusted for biologic naïvety, its superiority vanished and drug survival rates were similar for ixekizumab (91·6%), secukinumab (90·2%) and ustekinumab (92·8%), all of them superior to adalimumab (76·5%) and etanercept (71·9%) at 12 months and beyond. Besides biologic non‐naïvety (2·10, P < 0·001), the introduction of a new drug such as secukinumab or ixekizumab (relative hazard ratio 1·6, P = 0·001) and female gender (1·50, P = 0·019) increased the risk of treatment discontinuation overall, whereas psoriatic arthritis did not (1·12, P = 0·21). Conclusions: The time‐dependent availability of drugs should be considered when analysing and comparing drug survival. Previous biologic exposure significantly influences drug survival. Women are more likely to stop treatment. Abstract : What is already known about this topic? Female gender and previous biologic exposure have been discussed as predictors for decreased drug survival in patients with psoriasis, but it remains unknown whether a time‐dependent increased availability of treatment options alters biologic drug survival. What does this study add? The increased availability of alternative biologic treatments over time leads to an elevated risk for treatment discontinuation overall; therefore, drug survival analysis has to be time adjusted. Moreover, the study reveals that the impact of previous biologic treatment on drug survival is tremendous and confirms worse drug survival in female patients. Linked Comment: Gniadecki. Br J Dermatol 2021; 184 :996–997 .